2005
DOI: 10.1063/1.2046667
|View full text |Cite
|
Sign up to set email alerts
|

New observations on the luminescence decay lifetime of Mn2+ in ZnS:Mn2+ nanoparticles

Abstract: A fast decay emission peaking at 645 nm with a decay lifetime within the experimental resolution of 0.14 micros is observed in ZnS:Mn2+ nanoparticles. This short-lived signal is also observed in pure ZnS and MgS: Eu3+ nanoparticles, which has nothing to do with Mn(2+)-doped ions but is from the deep trap states of the host materials. The short-lived component decreases in intensity relative to the Mn2+ emission at higher excitation powers, while it increases in intensity at low temperatures and shifts to longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 20 publications
5
29
0
Order By: Relevance
“…Different groups (Xiao and Xiao 2008;Qu et al 2002;Yang et al 2003) have studied the origin of the blue emission from undoped ZnS nanoparticle synthesized through chemical method. Chen et al (2005) reported that the PL emission of ZnS nanoparticles is at 445 nm from donor-acceptor pair. The average size of the ZnS was 3 nm.…”
Section: Optical Absorptionmentioning
confidence: 99%
“…Different groups (Xiao and Xiao 2008;Qu et al 2002;Yang et al 2003) have studied the origin of the blue emission from undoped ZnS nanoparticle synthesized through chemical method. Chen et al (2005) reported that the PL emission of ZnS nanoparticles is at 445 nm from donor-acceptor pair. The average size of the ZnS was 3 nm.…”
Section: Optical Absorptionmentioning
confidence: 99%
“…Different metal ions such as Cu, Mn, Pb, Co, Cd, Eu, and Sm doped with ZnS have been studied by many researchers because of their extensive photoluminescence (PL) properties [7]. Generally ZnS doped with these metal ions provide new opportunities as full-color luminescence in the UV-visible region [8][9][10][11][12]. Recent studies on Y ions incorporated into wide band gap semiconductor like ZnO [13,14] which resulted in significant increase in the optical properties, photocatalyst efficiency with improved stability of ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Sapara et al reported PL emission at 425 nm from undoped ZnS sample due to the de-excitation of defect states upon 290nmUV excitation [23]. Chen et al also reported a PL emission peak at 445 nm from donor-acceptor pairs in undoped ZnS sample [24]. In recent reports, Kumbhakar et al reported the synthesis and optical properties of ZnS:Co and ZnS:Mn nanoparticles [20,25].…”
Section: Resultsmentioning
confidence: 94%